Silicosis - Ramírez, Augusto V. (2013)
Silicosis is a pneumoconiosis caused by repeated inhalation of silica dust, characterized by pulmonary fibrosis and a bronchitis component. It is predisposing factor for lung cancer and cause of temporary or permanent work disability. According to its presentation it may be classical, acute, complicated or accelerated. Peru is a mining country with more than 197 000 direct workers in this activity considered at high risk for developing silicosis. Clinical examination, labor history, lung X-rays and spirometry are basic in diagnosis. There is no treatment for silicosis. Prevention is the only known way to avoid it. In addition to collective and personal protection, main preventive action is education of workers and employers on risk of exposure to silica dust.